2019
DOI: 10.24843/eja.2019.v29.i02.p20
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Trust Dan E-Service Terhadap Repurchase Intention Bagi Pengguna Aplikasi Shopee

Abstract: ABSTRAKAplikasi modern tentunya membutuhkan sistem yang tersusun rapi, sehingga memudahkan konsumen untuk menggunakannya. Kepercayaan adalah hal penting yang diperlukan situs online karena secara logis konsumen memiliki tingkat risiko yang lebih tinggi dalam transaksi online dibandingkan dengan transaksi offline dalam hal pengiriman, pembayaran, dan informasi pribadi. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana trust dan e-service dapat mempengaruhi Repurchase intention pada pengguna aplikasi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
2
0
3
Order By: Relevance
“…clients are more inclined to buy from a company more than once if they trust the business and are aware that the firm provides the same goods, services, and security assurances to both online and offline clients. This study confirms the findings of Liang et al (2018), Nilasari (2019), Muchlis (2021), Iksan and Lestari (2021), and Dewi and Giantari (2022), demonstrating that trust has a favorable and statistically significant influence on the intention to make a purchase.…”
Section: The Impact Of Trust On Repurchase Intentionsupporting
confidence: 89%
See 1 more Smart Citation
“…clients are more inclined to buy from a company more than once if they trust the business and are aware that the firm provides the same goods, services, and security assurances to both online and offline clients. This study confirms the findings of Liang et al (2018), Nilasari (2019), Muchlis (2021), Iksan and Lestari (2021), and Dewi and Giantari (2022), demonstrating that trust has a favorable and statistically significant influence on the intention to make a purchase.…”
Section: The Impact Of Trust On Repurchase Intentionsupporting
confidence: 89%
“…The quality of an organization's e-services is measured by how smoothly and quickly customers may peruse the site, make a purchase, and get their order (Harahap et al, 2020). Nilasari (2019); Rohwiyati and Praptiestrini (2019); Anggraini et al (2021); Bello et al (2021);. Iksan and Lestari (2021) found that the quality of e-services had no effect on the likelihood of a customer making a repeat purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Konsumen biasanya akan melihat atau meninjau para pelanggan atas komentar pengalaman mereka setelah menggunakan atau pada saat menerima layanan secara online, apakah barang yang diminta sesuai dengan harapan atau tidak, apakah terjadi kesalahan atau kesesuaian jumlah item yang dipesan. Hal ini juga dapat dilihat dari hasil review atau testimoni dari konsumen yang menunjukan adanya kekecewaan atau ketidakpuasan konsumen atas barang yang diterima atau layanan yang tidak sesuai dengan harapan sehingga hal tersebut mempengaruhi konsumen lain dalam mempertimbangkan pembelian (Nilasari, 2019).…”
Section: Pendahuluanunclassified
“…One of the most commonly used methods is sales promotions such as price discounts, vouchers, cashback, free shipping and so on. Sales promotion is part of the promotional strategy carried out by the company with the aim of attracting consumer attention (Sari & Suriyadi, 2021). Based on the background of the problem, the aim of this research is to analyze the influence of brand ambassadors and sales promotion on online repurchase intention in online shopping studies at E-Commerce Tokopedia.…”
Section: Introductionmentioning
confidence: 99%